Smallpox lesion characterization in placebo-treated and tecovirimat-treated macaques using traditional and novel methods. - Todd M Bell; Paul Facemire; Jeremy J Bearss; Jo Lynne Raymond; Jennifer Chapman; Xiankun Zeng; Joshua D Shamblin; Janice A Williams; Douglas W Grosenbach; Dennis E Hruby; Inger K Damon; Arthur J Goff; et al. (PLoS Pathogens, 2024)
Smallpox was the most rampant infectious disease killer of the 20th century, yet much remains unknown about the pathogenesis of the variola virus. Using archived tissue from a study conducted at the Centers for Disease Control and Prevention we characterized pathology in 18 cynomolgus macaques intravenously infected with the Harper strain of variola virus. Six macaques were placebo-treated controls, six were tecovirimat-treated beginning at 2 days post-infection, and six were tecovirimat-treated beginning at 4 days post-infection. All macaques were treated daily until day 17. Archived tissues were interrogated using immunohistochemistry, in situ hybridization, immunofluorescence, and electron microscopy. Gross lesions in three placebo-treated animals that succumbed to infection primarily consisted of cutaneous vesicles, pustules, or crusts with lymphadenopathy. The only gross lesions noted at the conclusion of the study in the three surviving placebo-treated and the Day 4 treated animals consisted of resolving cutaneous pox lesions. No gross lesions attributable to poxviral infection were present in the Day 2 treated macaques. Histologic lesions in three placebo-treated macaques that succumbed to infection consisted of proliferative and necrotizing dermatitis with intracytoplasmic inclusion bodies and lymphoid depletion. The only notable histologic lesion in the Day 4 treated macaques was resolving dermatitis; no notable lesions were seen in the Day 2 treated macaques. Variola virus was detected in all three placebo-treated animals that succumbed to infection prior to the study's conclusion by all utilized methods (IHC, ISH, IFA, EM). None of the three placebo-treated animals that survived to the end of the study nor the animals in the two tecovirimat treatment groups showed evidence of variola virus by these methods. Our findings further characterize variola lesions in the macaque model and describe new molecular methods for variola detection.